Peganum harmala intoxication, a case report - Mohammad Moshiri; Leila Etemad; Soheila Javidi; Anahita Alizadeh (Mashhad University of Medical Sciences, 2013)
Objective: Peganum harmala (P. harmala), "Espand" in Persian, has small seeds and has been used in traditional medicine as emmenagogue and an abortifacient. It has various pharmacological effects such as antifungal, antibacterial, hypothermic, anticancer, antinociceptive, and reversible monoamine oxidase inhibition. Case details: This case was a 45 years old woman who ingested about 50 grams seed of P. harmala for hypermenorrhae. She suffered nausea, vomiting, dizziness, tremor, ataxia, and confusion. On physical examination, she had hypotension (BP=90/60 mmHg) with normal heart rate (60 beat/min) and impaired knee to heel test. Her consciousness was reduced without any hallucination. Her laboratory test was normal. She was discharged at good condition 18 hours later. Conclusion: In conclusion, physicians working in Iran and other regions that P. harmala is prescribed or used illegally, should know signs and symptoms of its toxicity in order to be able to deal with the emergencies, however, prognosis of these toxicity is not bad.